2015
DOI: 10.1007/s40520-015-0478-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of outcomes in elderly patients with acute ischemic stroke in China

Abstract: Stroke subtype and severity were associated with stroke outcomes among elderly patients in northern China. These findings suggest that it is crucial to highlight the affected factors of stroke outcome among elderly patients for reduce the burden of stroke in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Several studies showed that low-level of cholesterol was significantly associated to the poor outcome after acute ischemic stroke 1214 . Similarly, a previous study showed that a lower cholesterol level was associated with an increased risk of death among elderly patients with ischemic stroke 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that low-level of cholesterol was significantly associated to the poor outcome after acute ischemic stroke 1214 . Similarly, a previous study showed that a lower cholesterol level was associated with an increased risk of death among elderly patients with ischemic stroke 15 .…”
Section: Discussionmentioning
confidence: 99%
“…All patients in this study were identified from the stroke registry of the Department of Neurology, Jiamusi University First Hospital, China between January 2008 and December 2016. The inclusion criteria of participants and study design have been described previously 12 . In brief, all consecutive patients with first-ever acute ischemic stroke who were admitted to the Department of Neurology, Jiamusi University First Hospital within 72 hours of stroke onset were recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…This study used data from a stroke registry in the Department of Neurology, Jiamusi University First Hospital, China; the inclusion criteria for stroke patients have been described in a previous study [ 37 ]. Briefly, we prospectively collected data on the clinical characteristics and outcomes for all ischemic stroke patients who were admitted to the department between January 2008 and December 2013.…”
Section: Methodsmentioning
confidence: 99%
“…This study used data from a stroke registry in the Department of Neurology, Jiamusi University First Hospital, China; the inclusion criteria for stroke patients have been described in a previous study (Wu et al, 2015 ). Briefly, we prospectively collected data on the clinical characteristics and outcomes for all ischemic stroke patients who were admitted to the Department of Neurology, Jiamusi University First Hospital, China between January 2008 and December 2013.…”
Section: Methodsmentioning
confidence: 99%